Will the "top five" deepest trenches lose one of their members?. (February 2020) - Dreutter, Simon; Steffen, Melanie; Martínez Arbizu, Pedro; Brandt, Angelika
Abstract: The Kuril-Kamchatka Trench is considered one of the five deepest trenches on the planet with depths over 10, 000 m. It has been visited and surveyed by multiple ships over the years with different depth measurement results. Newly acquired multibeam echosounder data from RV Sonne cruise SO250 now confirmed what some of the historic surveys already stated. The Kuril-Kamchatka Trench does not reach depths up to 10, 542 m at the location where this depth value has been reported, but is with 9604 m almost 1000 m shallower in its deepest depression of the SO250 survey area. The originally reported deepest location of the trench, the Vityaz Deep 3, lies roughly 107 nautical miles southeast of the newly surveyed deepest location and shows a depth of only 7920 m.